The Influence of Human Resource Development, Discipline, and Job Characteristics on Employee Achievement in The Medan Hajj Dormitory - Silaen, Lisna Riany; Syahputra, Dedy; Hutagalung, Daniel Jefri Manatap; Simanjuntak, Jenny Fransiska; Supriadi, Supriadi; Nasti, Nilawati (Mahesa Research Center, 2024)
This study explores the effects of job characteristics, discipline, and human resource development on employee job satisfaction at UPT Medan Embarkation Hajj Dorm. The research targets all 60 employees of this facility, utilizing multiple linear regression analysis to examine the data. The results reveal that human resource development has a moderate impact on employee performance, while discipline also plays a partial role. However, job characteristics are found to have a significant influence on employee satisfaction. Furthermore, the study highlights that the combination of effective human resource development, consistent disciplinary practices, and well-defined job characteristics dramatically enhances employee performance. These findings underscore the importance of a holistic approach to managing human resources, suggesting that integrating these elements can lead to improved job satisfaction and overall employee effectiveness. This comprehensive analysis provides valuable insights for organizational strategies aimed at boosting employee engagement and productivity.